Determining the preliminary performance of selected Annonaceae cultivars in subtropical conditions - Chagas, Pollyana Cardoso; Crane, Jonathan; Chagas, Edvan Alves; Vendrame, Wagner; Costa, Barbara Nogueira Souza; Neto, Aurélio Rubio; Moura, Elias Ariel (Comunicata Scientiae, 2022)
Plants phenology is extremely important tool for crop management, crop manipulation, and marketing. The objective of this research was to investigate the phenology and fruit quality of the several Annonaceae species under subtropical conditions of Homestead, Florida, USA. The study was carried out in an experimental sugar apple (Annona squamosa L.), orchard with cultivars: 'LeahReese', 'Lessard Thai' and 'Red' and the atemoya ‘Gefner’ (A. cherimola x A. squamosa L). Ten uniformly vigorous and healthy plants of each cultivar were selected. The fruit harvest period was similar for all the cultivars, except for sugar-apple 'LeahReese', which had the shortest harvest period of only 41 days. Multivariate analysis showed that 'Lessard Thai' and 'Red' sugar apple cultivars had smaller sizes and lower chemical quality. Cultivar "LeahResse" had the highest fruits, in addition, a strong correlation with the atemoya hybrid "Gefner". The sugar apples ‘Lessard Thai’ and 'Red' had similar phenology and had a 166-day pruning to harvest cycle. In contrast, 'LeahReese' sugar apple and 'Gefner' atemoya had significantly longer cycles of 182 and 196 days, respectively. The sugar apple 'LeahReese' had the best physical characteristics of the cultivars investigated, while the atemoya 'Gefner' had the best physiochemical characteristics and the longest shelf life.